O tempo livre e a produção da existência da juventude do campo: um estudo com jovens estudantes do Assentamento João Batista II - PA - NASCIMENTO, Tábita Cristina Modesto (Universidade Federal do Pará, 2017)
Time is a historical construction, that is to say, it is a construction fruit of the moderni-zation of the society, that was being shaped along the development of the modes of production and incorporating elements of these in its definition. The notions of time vary culturally and historically and for class reasons. In the society of capital, for the bourgeois class time takes on proportions linked to productivism and profit-making. For the working class, time is closely related to the presupposition of all human exist-ence, its first historical act, the production of means for the satisfaction of the neces-sities of its material life. In this same society, Time considered Free, as it has been characterized today, is also closely linked to the process of constitution of the capital-ist system, in this way, it assumes the premise of being that time left over after com-pleting the work day. This research aims to analyze the use of Free Time of young students of the School of the Field, starting from the identification and categorization of the activities developed by young people in their daily lives. A field survey was car-ried out with 27 young people, of whom 16 were male and 11 were female. As a data collection instrument, a questionnaire and interviews with community leaders were used. As Analysis methodology, Content Analysis was used. The first results to which we have arrived through show the need for more scientific research, mainly at the national level, on Free Time and Youth, as Free Time is reflected in most studies, That is, only as a space to think about the practices of physical activities, without a look at the totality of facts and the historical understanding of Time. Other results that we have obtained through the field research highlight differences by gender in the occupation of residual time, that is, the young women spend their time with domestic activities and the young men end up performing other leisure activities more fre-quently. We also noticed that young people are mostly developing leisure-time activi-ties such as "watching television", "accessing the internet" and "using the cell phone", which are also influenced by technological advances and lack of spaces and oppor-tunities in the community. We also conclude that the young people in the João Batis-ta II Settlement have not yet overcome in their Free Time the mere reproduction of activities carried out by the media (such as playing football and using social net-works), both for lack of choice (since the public power Municipal social policies of sport and leisure), as well as for the lack of understanding of the possibilities of emancipation arising from residual time.